Development of a Two-Channel Simultaneous Photoplethysmography Recording System - Kim Soon Chong; Kok Beng Gan; Mohd. Ali Mohd. Alauddin (Journal of ICT Research and Applications, 2012)
Multi-site photoplethysmograph  (PPG) recording enables researchers to study the vascular and hemodynamic  properties of human subjects. Currently, there  is  no  commercial  system  available  in  the  market  to  perform  either  one channel or multi-channel PPG recording. PPG is an optoelectronic technique that measures  changes  in  blood  volume  associated  with  cardiac  contraction.  The measurements  can  be  obtained  from  fingertips,  ear  lobes  and toes  due  to  their low absorption and high degree of vasculature. The main objective of this project is to develop a two-channel simultaneous PPG recording system to acquire PPG signals  from  two  different  physiological  sites  using  a  Nellcor  equivalent  PPG probe.  MATLAB  software  was  used  during  the  development  phase  to  ensure rapid prototyping. The experiment results show that there was no inter -channel delay in the developed two-channel PPG system. Our preliminary results show that the delays between the left and the right arm were from 4 to 12 ms in three healthy random subjects. The system is portable, powered by universal serial bus (USB) and allows the user to do the PPG data acquisition in a clinical setting.